2019
DOI: 10.9734/ijpss/2019/v30i430183
|View full text |Cite
|
Sign up to set email alerts
|

Status of Available Phosphorus and Forms of Phosphorus in Soil under Major Cropping Systems of Y.S.R. Kadapa District, A.P.

Abstract: An investigation was carried out to study different forms of phosphorus under major cropping systems in Y.S.R. Kadapa district of Southern Zone of Andhra Pradesh. Five soil samples from each cropping system at 0-15 cm depth collected from each cropping system to study their physicochemical properties, status of available P2O5 and different forms of P. Majority of the soils were moderately alkaline in reaction, non-saline, free lime content indicating that these soils are moderately calcareous, medium to high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…It is generated by free radicals that cause membrane lipid peroxidation and has been shown to deplete antioxidant levels, increase proinflammatory cytokines, and increase oxidative stress [56]. The present study confirmed previous reports of increased MDA levels in participants with malaria compared with uninfected controls [7,[34][35][36][37][38][39][40][41][42][43][44][45][47][48][49][50][53][54][55]. It is possible that lipid peroxidation on erythrocyte membranes-which are vulnerable to oxidative damage-is the cause of the elevated MDA levels found in malaria patients.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It is generated by free radicals that cause membrane lipid peroxidation and has been shown to deplete antioxidant levels, increase proinflammatory cytokines, and increase oxidative stress [56]. The present study confirmed previous reports of increased MDA levels in participants with malaria compared with uninfected controls [7,[34][35][36][37][38][39][40][41][42][43][44][45][47][48][49][50][53][54][55]. It is possible that lipid peroxidation on erythrocyte membranes-which are vulnerable to oxidative damage-is the cause of the elevated MDA levels found in malaria patients.…”
Section: Discussionsupporting
confidence: 88%
“…This disparity may be attributed to the more severe nature of P. falciparum infection, which induces greater oxidative stress in the host cells. However, another study found lower MDA concentrations in P. falciparum malaria than in P. vivax malaria [41]. This discrepancy may be explained by the increased susceptibility of patients with P. vivax malaria to oxidative stress, potentially due to lower levels of ascorbic acid [53].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations